Human Capital or Cultural Taxation: What Accounts for Differences in Tenure and Promotion of Racialized and Female Faculty? - Wijesingha, Rochelle; Ramos, Howard (Canadian Journal of Higher Education, 2017)
Achieving tenure and promotion are significant milestones in the career of a university faculty member. However, research often indicates that racialized and female faculty do not achieve tenure and promotion at the same rate as their non-racialized and male counterparts. Using new original survey data on faculty in eight Canadian universities, this paper examines differences in tenure and promotion among racialized and female faculty and investigates the extent to which explanations of human capital theory and cultural or identity taxation account for these disparities. Logistic regression confirms that controlling for human capital and cultural or identity taxation washes away the differences between male and female faculty for achieving both tenure and promotion. However, differences for racialized faculty remain, thereby offering evidence of discrimination in the academic system.